2010
DOI: 10.1111/j.1651-2227.2010.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with type 1 diabetes and risky behaviour

Abstract: Adolescents with T1DM are as likely as their healthy peers to engage in risky behaviour, indicating the potential benefit of anticipatory guidance concerning glycaemic control and increased risk of acute and chronic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 29 publications
6
58
1
1
Order By: Relevance
“…Given that adolescence is the period where tobacco use is initiated (Moolchan et al, 2003), adolescents displaying diabetes may be particularly attracted to tobacco products. Indeed, smoking rates in adolescents with type 1 diabetes have been reported to be significantly higher compared to healthy controls (47% vs 38%; Scaramuzza et al, 2010). The latter study also reported higher rates of illicit drug use and risky sexual behavior in young persons with diabetes.…”
Section: Problem Of Tobacco Use In Persons With Diabetesmentioning
confidence: 88%
“…Given that adolescence is the period where tobacco use is initiated (Moolchan et al, 2003), adolescents displaying diabetes may be particularly attracted to tobacco products. Indeed, smoking rates in adolescents with type 1 diabetes have been reported to be significantly higher compared to healthy controls (47% vs 38%; Scaramuzza et al, 2010). The latter study also reported higher rates of illicit drug use and risky sexual behavior in young persons with diabetes.…”
Section: Problem Of Tobacco Use In Persons With Diabetesmentioning
confidence: 88%
“…Thus, this group is doubly disadvantaged and may be more vulnerable to adverse health outcomes (Saunders, 2011;Scaramuzza et al, 2010). In Portugal, the studies Health Behaviour School-Aged Children (HBSC) (Matos & Equipa Aventura Social, 2000 and Kidscreen (Gaspar & Matos, 2008) have been also pointing out higher vulnerability in this population.…”
Section: Introductionmentioning
confidence: 97%
“…Much of the clinical work in this area has focused on patients with type 1 diabetes, which is a condition that produces little to no release of insulin from the pancreas. Smoking rates in adolescents with type 1 diabetes are higher than healthy controls (47 versus 38 %; [58]). Also, persons with type 1 diabetes report higher rates of current smoking (12.3 %) as compared to non-diabetic subjects (8.6 %; [59]).…”
Section: Tobacco Use In Vulnerable Populationsmentioning
confidence: 97%